Design of BN porous sheets with richly exposed (002) plane edges and their application as TiO2 visible light sensitizer. (September 2015) - Weng, Qunhong; Ide, Yusuke; Wang, Xuebin; Wang, Xi; Zhang, Chao; Jiang, Xiangfen; Xue, Yanming; Dai, Pengcheng; Komaguchi, Kenji; Bando, Yoshio; Golberg, Dmitri
Abstract: Hexagonal boron nitride ( h -BN) exhibits a wide band gap of 5.5 eV, and is well known for its high thermal and chemical inertness. Thus, it is commonly considered that h -BN is inappropriate for photocatalysis and photovoltaic conversion applications. Here, we show that the rationally designed BN porous sheets (BNPS) with richly exposed (002) plane edges (functionalized with hydroxyl groups) exhibit wide-spectrum light absorptions in both UV and visible light ranges. Such intriguing property is seldom reported for any BN materials in experiments. After hybridizing with anatase TiO2 nanoparticles, the resultant TiO2 /BNPS composite becomes a potent visible-light photocatalyst for organic compound oxidative degradations. These results confirm that the designed BNPS can efficiently act as an inorganic sensitizer to induce the visible light response of TiO2 . Graphical abstract: Highlights: Boron nitride porous sheets with richly exposed (002) plane edges (terminated with hydroxyl groups) have wide-spectrum UV/Vis absorptions. Boron nitride porous sheets can function as an inorganic sensitizer to induce the visible light response of TiO2 . The as-prepared TiO2 /BNPS composite shows advanced photocatalytic degradations of organic compounds under visible light irradiations.